Relationship between Perceived Spousal Social Support and Blood Pressure Control among Hypertensive Patients Attending General Outpatient Clinic in Federal Teaching Hospital, Ido-Ekiti, Nigeria - Ekundayo OO; Elegbede OT; Gabriel-Alayode OE; Agboola SM; Shabi OM; Bello IS; Omosanya OE; Ajetunmobi OA; Fashola AM (Archives of Clinical Hypertension - Peertechz Publications, 2020)
Background: Despite many approaches to control hypertension, a lot of people still experience challenges keeping their Blood Pressure (BP) under control, and because the condition requires life - long treatment, many patients will need additional effort from their spouses. The spouse shares intimacy with patient and is the chief source of social support that provides financial assistance, reminds and encourages medication use, shows concern and interest by discussing issues related to the disease. Therefore, exploring the relationship between Perceived Spousal Social Support (PSSS) and BP control will help the physician and other stakeholders harness the gains of this association to achieving BP control, prevent complications and death associated with hypertension. Objective: To identify the relationship between perceived spousal social support and blood pressure control among hypertensive patients attending General Outpatient Clinic (GOPC) in Federal Teaching Hospital, Ido-Ekiti, Nigeria. Materials and methods: This was a hospital - based cross - sectional study carried out between June and August 2016 among 298 hypertensive patients aged 18 and 65 years attending GOPC of the Federal Teaching Hospital, Ido Ekiti. Collection of data was done using pre-tested, semi-structured questionnaire on sociodemographic characteristics, blood pressure measurement and 4-point Likert Social Support questionnaire to measure the perceived spousal social support. Data was analysed using SPSS IBM version 17.0. Results: Mean age of respondents was 56.0 ± 8.5 years and seventy percent were females with male to female ratio of 1:2.3. Less than half of the respondents, 47.7% and about half of the respondents, 50.3% achieved BP control and demonstrated strong PSSS respectively. There was statistically significant relationship between PSSS and BP control (χ2 = 27.05, p < 0.001).  Conclusion: Social support perceived by participants positively influenced their BP control. Family Physicians and other health care providers should therefore determine and enhance the level of this support and encourage spouses to provide this support for their partners who have hypertension or those having difficulty controlling their BP despite the appropriate use their medications.